O čem se nemluví: Příspěvek k problematice sexuality terénního výzkumníka. - Gabriela Fatková (Gender a Výzkum, 2013)
The essential attribute of socio-cultural anthropology and ethnography – fieldwork – is a process that interferes in the intimate lives of the population under observation, and that of the researcher as well. This study reconceptualises the issue of sexuality and gender, as they are for the individual the primary characteristic which determines a researcher’s position in field. The article highlights the discrepancy between the way fieldwork techniques are taught, and the real practice of fieldwork. One solution could entail relaxing methodological formalism, which may be in practice unachievable, and the removal of the taboo surrounding the whole issue. Different strategies for dealing with the researchers’ own sexuality and gender in the field, and their accompanying adaptation to the situation, are considered. Attention is paid to the issue of sexual violence in fieldwork.